Embedded in the land: Customary social relations and practices of resilience in an East Timorese community - Stead, Victoria (The Australian journal of anthropology, 2012)
Drawing on a case study of Cacavei, a rural subsistence community in Timor-Leste, this article explores the mutually constitutive relationship between people and land within customary forms of society. Patterns of land use and connection to land are not simply reflective of genealogical modes of social organisation, but are also enabling of them. Particularly, the embedding of ancestors within the land offers a means of accessing kinship relationships beyond the genealogical present. Embeddedness provides a quality of embodiment that makes ancestors active participants in social life. Constituted in the relational nexus of people and land, forms of social organisation in Cacavei have a mutability which goes some way to explaining the community’s resilience in spite of forced displacement and cultural disruption during the period of Indonesian occupation. This mutability might be considered more broadly as a source of resilience for customary communities grappling with modernising processes of change.